Comparative effects of antiretroviral treatments on metabolomics, cytokine profiles and platelet activation in HIV-positive individuals - Steel, Helen Carolyn (University of Pretoria, 2023)
Dissertation (MSc (Medical Immunology))--University of Pretoria, 2023.